Metabolomics and proteomics reveal drought-stress responses of leaf tissues from spring-wheat - Michaletti, Anna (Sci Rep, 2018)
To reveal the integrative biochemical networks of wheat leaves in response to water deficient conditions, proteomics and metabolomics were applied to two spring-wheat cultivars (Bahar, drought-susceptible; Kavir, drought-tolerant). Drought stress induced detrimental effects on Bahar leaf proteome, resulting in a severe decrease of total protein content, with impairments mainly in photosynthetic proteins and in enzymes involved in sugar and nitrogen metabolism, as well as in the capacity of detoxifying harmful molecules. On the contrary, only minor perturbations were observed at the protein level in Kavir stressed leaves. Metabolome analysis indicated amino acids, organic acids, and sugars as the main metabolites changed in abundance upon water deficiency. In particular, Bahar cv showed increased levels in proline, methionine, arginine, lysine, aromatic and branched chain amino acids. Tryptophan accumulation via shikimate pathway seems to sustain auxin production (indoleacrylic acid), whereas glutamate reduction is reasonably linked to polyamine (spermine) synthesis. Kavir metabolome was affected by drought stress to a less extent with only two pathways significantly changed, one of them being purine metabolism. These results comprehensively provide a framework for better understanding the mechanisms that govern plant cell response to drought stress, with insights into molecules that can be used for crop improvement projects.